Research on computing resource allocation strategy for cloud radio access network based on demand forecasting - Zhipeng WANG; Bin CAO; Qinyu ZHANG (物联网学报)
Cloud radio access network(CRAN) is a new network architecture commonly used in 5G network.It uses network function virtualization and software defined network technology to support end-to-end network slicing so that access network can share the same infrastructure.A computing resource allocation scheme based on virtualized network function(VNF) computing resource demand forecasting was proposed for cloud wireless network supporting end-to-end network slicing.Data-driven operation and maintenance framework established by the control plane collects network information and performs data processing to predict the demand for computing traffic in a period of time,which used the discrete particle swarm optimization based on best-fit-decreasing to dynamically and dynamically allocate CRAN computing resources,reducing the migration energy consumption and migration times of VNF.